2023
DOI: 10.1007/s13224-022-01719-7
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-Based Training on Basic Obstetrics and Gynecology Ultrasound Skills During COVID Pandemic

Abstract: Background COVID-19 pandemic led to an alarming rise in sickness absenteeism among the radiologists. Anticipating a continued shortage of experienced radiologists in future COVID waves, it is essential to train the medical professionals in basic skills related to ultrasonography to enable them to perform basic Obstetrics and Gynecology (OG) scans safely in emergencies. Virtual reality simulation training is an alternative to conventional ultrasound training. Methods A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…SBME presents significant potential for OB/GYN US training. It affords trainees a risk-free environment in which to practice and refine their skills, boosting their confidence before transitioning to real patient interactions [41][42][43] . US simulators, comprising a human model and a mock probe connected to a computer monitor, allow trainees to practice transabdominal and transvaginal OB/GYN US procedures and aid in evaluating their competence 44 .…”
Section: Is Simulation-based Education Effective For Ob/gyn Ultrasoun...mentioning
confidence: 99%
See 2 more Smart Citations
“…SBME presents significant potential for OB/GYN US training. It affords trainees a risk-free environment in which to practice and refine their skills, boosting their confidence before transitioning to real patient interactions [41][42][43] . US simulators, comprising a human model and a mock probe connected to a computer monitor, allow trainees to practice transabdominal and transvaginal OB/GYN US procedures and aid in evaluating their competence 44 .…”
Section: Is Simulation-based Education Effective For Ob/gyn Ultrasoun...mentioning
confidence: 99%
“…SBME primarily aims to foster automaticity in hand-eye coordination, thereby freeing cognitive resources to focus on complex tasks, such as image interpretation and patient communication. Studies have demonstrated both immediate [41][42][43][45][46][47][48][49][50][51][52][53] and sustained improvements in knowledge, performance, image quality and diagnostic accuracy through the use of SBME 15,54,55 . However, the effectiveness of SBME is not unchallenged.…”
Section: Is Simulation-based Education Effective For Ob/gyn Ultrasoun...mentioning
confidence: 99%
See 1 more Smart Citation